Equity, Equality and Diversity in the Nordic Model of Education - Frønes, Tove Stjern; Pettersen, Andreas; Radišić, Jelena; Buchholtz, Nils (Springer Nature, 2020)
Does the Nordic model of education still stand by its original principles and safeguard education for all? This Open Access volume is a carefully crafted collection of chapters that investigate the different aspects of equity, equality and diversity across the education systems in the Nordic countries. Based on data from various national and international large-scale assessments, the volume provides a better understanding of both the functions and foundations of the Nordic model, along with how the concepts mentioned above are enacted in practice. Across the chapters, data from different national and international large-scale assessment studies are used for cross- and single-country analyses on a variety of issues related to equity, equality and inequality in diverse educational settings. The investigations address different subject domains (i.e., mathematics, science, reading), age and grade groups, but also issues related to teachers and the schools themselves. In addition to these empirical chapters, the book addresses the theoretical and methodological underpinnings of the ideas and tools embedded in the phenomena of equity and equality and how they have met in the Nordic model of education.